Morphology of internal thoracic and radial arteries at patients subjected to coronary artery bypass grafting - S. Ye. Mamchur; Yu. Yu. Vechersky; M. V. Fadeyev (Бюллетень сибирской медицины, 2004)
Peculiarities of internal thoracic and radial artery morphology (ITA and RA) have been investigated by light microscopy in continuous sampling of 10 patients subjected to coronary artery bypass grafting. The object of investigation has been ITA and RA segments marked out during the surgery, fixed in formalin and colored by hematoxylin and eosin. As a result it has been found that the frequency of ITA and RA intima thickening was 28,1 and 20% of cases respectively in CABG candidates. The ratio of intima-media thickness in RA was 2,5 times higher than in ITA. This ratio in distal parts of ITA was 2,3 times higher than in proximal ones and 1,7 times higher than in middle ones. This fact is evidence of the need to decline the use of ITA distal segment in case of enough ITA length.